Acute Epstein-Barr Virus Hepatitis in a 32 Month Old Female Manifesting as Henoch-Schönlein Purpura - Hee Jin Kim; Su Jin Jung; Jun Ho Lee (Korean Society of Pediatric Nephrology, 2015)
Henoch-Schönlein purpura can result from exposure to an antigen after infection with several types of organisms. However, Henoch-Schönlein purpura caused by a primary Epstein-Barr virus infection has been rarely reported. Here, we report the case of a 32-month-old female patient who presented with Henoch-Schönlein purpura. Based on abnormal liver function test results and positive results for Epstein-Barr virus infection markers, a diagnosis of Epstein-Barr virus hepatitis manifesting as Henoch-Schönlein purpura was made. Treatment with methylprednisolone and hydration improved the symptoms, and a switch to oral steroids was effective in completely alleviating the purpura. No recurrence was noted and no liver function abnormalities were detected during the follow up period.